Neshat-isms - Neshat, Shirin 1957- (Princeton University Press, 2024)
"A collection of quotations from the influential contemporary Iranian visual artist Shirin Neshat"--
Keywords: Neshat, Shirin -- 1957-; Neshat, Shirin / 1957- / Quotations; Neshat, Shirin / 1957-; Quotations; Zitatensammlung